Nebivolol Increases Nitric Oxide Synthase via beta(3) Adrenergic Receptor in Endothelial Cells Following Exposure to Plasma from Preeclamptic Patients - Bueno-Pereira, Thaina Omia [UNESP]; Nunes, Priscila Rezeck [UNESP]; Matheus, Mariana Bertozzi [UNESP]; Vieira da Rocha, Ananda Lini [UNESP]; Sandrim, Valeria Cristina [UNESP] (Mdpi, 2022)
Background: Low bioavailability of nitric oxide (NO) is related to the pathophysiology of preeclampsia (PE). In the present study, we investigated the effect of nebivolol (NEB), a beta(3)-receptor agonist with vasodilator properties, on the NO synthesis in endothelial cells incubated with plasma from preeclamptic patients. Methods and results: Human umbilical vein endothelial cells (HUVECs) were incubated with plasma from healthy pregnant (HP) and PE women; NO quantification was assessed by a fluorescence compound. We found that endothelial cells incubated with plasma from women with PE show lower NO levels compared with the HP group (p < 0.0001). However, NEB treatment increases NO levels, partially, mediated by beta(3) adrenergic receptors (p < 0.0001) and through eNOS activation (p < 0.0001). Conclusions: Our results suggest that NEB acts in NO synthesis through eNOS activation and beta(3) adrenergic receptors in the endothelium. However, further studies will be needed to understand this molecule.
Keywords: nebivolol; nitric oxide; adrenoceptor; preeclampsia; endothelial dysfunction